2018
DOI: 10.1590/2175-35392018039914
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias por sexo en la intimidación escolar y la resiliencia en adolescentes

Abstract: Resumen El objetivo de investigación es establecer las diferencias por sexo entre la intimidación escolar y la resiliencia en adolescentes de instituciones educativas públicas de Bogotá. Se realizó un diseño de investigación no experimental transversal descriptivo-comparativo, se seleccionaron 354 participantes con edades entre 12 y 18 años. Se aplicaron la Escala de Resiliencia (Wagnild & Young, 1993) y el Cuestionario de Intimidación Escolar Abreviado CIE - A (Moratto, Cárdenas, & Berbesí, 2012). Los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
3
1
3
Order By: Relevance
“…Likewise, the present study shows a higher resilience variable level for boys than girls, meaning that H3 is not met either. As with the EI variable, some controversy exists regarding resilience since we find studies that have different research results to those of our study, such as the works by De la Fuente et al ( 2017), García et al (2019), andRomero et al (2018), in which no significant differences in resilience were found between men and women. Nonetheless, our results do coincide with some other studies, such as those of Fínez andMorán (2017), andGonzález et al (2008).…”
Section: Discussioncontrasting
confidence: 83%
“…Likewise, the present study shows a higher resilience variable level for boys than girls, meaning that H3 is not met either. As with the EI variable, some controversy exists regarding resilience since we find studies that have different research results to those of our study, such as the works by De la Fuente et al ( 2017), García et al (2019), andRomero et al (2018), in which no significant differences in resilience were found between men and women. Nonetheless, our results do coincide with some other studies, such as those of Fínez andMorán (2017), andGonzález et al (2008).…”
Section: Discussioncontrasting
confidence: 83%
“…Por otro lado, la investigación realizada por Bosa et al (2018) en cuatro instituciones educativas con una muestra de 354 estudiantes entre los 12 y 18 años, analizó las diferencias de sexo en el comportamiento de acoso escolar, evidenciando que los hombres presentaron una mayor tendencia a incurrir en comportamiento de acoso escolar que las mujeres. Otro estudio realizado en China con 855 jóvenes mostró diferencias de sexo en el acoso cibernético, evidenciando promedios significativamente más altos en los hombres que en las mujeres en las dimensiones de ciberacosador y víctimas de ciber acoso (Zhou et al, 2019).…”
Section: Diferencias De Sexo En La Desvinculación Moral El Acoso Y El...unclassified
“…Similar to their peers around the world, adolescents from LAC countries who experience bullying victimization are also more likely to report mental health problems (BOSA ET AL., 2018). Studies in the region also point that victimization is not equal across groups, and both students with disabilities (VEGA LÓPEZ ET al., 2013) and LQBTQ students tend to be at higher risk of bullying (KOSCIW, 2019).…”
Section: Latin Americamentioning
confidence: 99%